Design of a morphing leading edge as a high lift device for a regional aircraft. Issue 1 (January 2021) - Contell Asins, C; Landersheim, V; Wacker, J-D; Adachi, S; Arnold-Keifer, S; May, M
Abstract: Morphing technologies can provide a significant contribution to reduction of noise and fuel consumption for future aircraft. In the framework of the European Aviation research programme Clean Sky 2, a design of a morphing leading edge was developed, which allows the simultaneous increase of wing chord and camber to adapt the airfoil to different airspeed conditions. The final design has a sliding contact at the bottom, whereas the upper surface is continuous with variable camber. In contrast to classical high lift devices, the lift coefficient can be increased without adding sources for turbulences at the upper wing surface. CFD analyses have been performed in order to quantify the aerodynamic performance of the designed morphing leading edge. Furthermore, a design concept both for the skin and for the actuation system is presented. The skin is designed using carbon fiber reinforced plastics (CFRP). In order to achieve both the required stiffness and flexibility, a customized non-constant layup is developed. Its feasibility for the high deformations during morphing is demonstrated by means of both numerical analysis and experimental validation. The electro-mechanical actuation system is designed to completely fit inside the morphing leading edge while still considering space for other subsystems. Besides the space requirements also weight, mountability and bird strike aspects are taken into account. Altogether, for the overall design of a morphing system is presented in this paper, various design challenges are highlighted and appropriate solutions for these challenges are discussed.